Investigation of a PCM-based latent heat storage system combined with an adiabatic compressed air energy storage system in a renewable energy context - Tony Karam; Chantal Maatouk; Elias Al Sarraf (Center of Biomass & Renewable Energy (CBIORE), 2026)
The intermittent nature of renewables has increased the reliance on energy storage technologies to boost the efficiency and stability of power systems. Adiabatic Compressed Air Energy Storage (A-CAES) systems, which recover and reuse the heat generated during compression, have attracted significant attention in recent years. While A-CAES combined with thermal energy storage (TES) systems show promising potential, especially in renewable-integrated power systems, their commercial implementation remains limited, with only a few A-CAES power plants operating and which rely solely on sensible heat storage. The relatively low energy density of sensible heat storage opens the door to exploring latent heat storage (LHS) systems using Phase Change Materials (PCM’s), which could play a significant role in enhancing the performance of A-CAES systems. Although high-temperature PCM’s have demonstrated efficiency benefits in concentrated solar plants and energy-intensive industries, their integration into A-CAES systems requires further exploration. Accordingly, this paper aimed at simulating and assessing the performance of a combined A-CAES and PCM-based LHS system coupled to a gas turbine and an air turbine, alongside a wind farm. The simulations were conducted for charging durations ranging between 2 and 10 hours, with a fixed 2-hour discharge operation. The resulting fuel-saving efficiency in the gas turbine configuration improved with extended charging durations, ranging between 63.8 % and 66.1%. Furthermore, the exergetic roundtrip efficiency remains higher in the gas turbine configuration for charging durations shorter than 7 hours. Beyond this threshold, however, the air turbine configuration becomes more appealing when the combined CAES–LHS systems are coupled to it, exhibiting higher exergetic roundtrip performance under extended charging conditions. These findings, although theoretical in nature, could serve as a starting point for estimating the performance of the combined CAES-LHS systems and promoting their deployment into power generation applications in a renewable energy context.